HUBUNGAN KECERDASAN INTERPERSONAL DENGAN KETERAMPILAN MENGELOLA KELAS PENDIDIK PAUD DI KECAMATAN GUNUNG RAYA KABUPATEN KERINCI PROPINSI JAMBI - Rizki Surya Amanda Surya Amanda; Daviq Chairilsyah Chairilsyah; Yeni Solfiah Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Absract: This study has to purpose the correlation of  interpersonal intelligence and classroom management skills of early childhood educators in district Gunung Raya, Kerinci Regency. Population in this research were all early childhood educators in district Gunung raya formal and non-formal a total of 64 people. Used the sample is saturated sample mean population is sampled. The collection of data technique is used questionnaire. Data analysis using descriptive analysis and correlation analysis product moment had tated previously assumptions. The result showed that there is a relationship between interpersonal intelligence and classroom management skills. It is seen from r amounted 0,590. Keywords : Relationship, interpersonal intelligence, classroom management skill